Fundamentals of Wireless Communication - Tse(3, (BDavids; Viswanath(3, (BPramods (New york Cambridge University, 2005)
this book is aweb of interlocking concepts the concepts can be structured roughly into three levels channel characteristics and modeling communication concepts and techniques application of these concepts in a System context
Includes Bibliograph, Referance and Index
12
Keywords: Wireless Communication System